OPTIMALISASI BIAYA PENDISTRIBUSIAN PRODUK TAUGE MOYASHI PADA CV SUMBER URIP FARM MENGGUNAKAN MODEL TRANSPORTASI - Dewati, Salma Putri; Khoerunnisa, Fani Latfiana; Salsabilasani, Falia; Zhafir, Farhan; Husyairi, Khoirul Aziz; Ainun, Tina Nur (LPPM-ITEBA, 2024)
Sufarm is an agricultural company that has been established since 1996. Currently, Sufarm focuses on supplying various high-quality bean sprouts and mushrooms to consumers and meeting the needs of the B2B market such as E-commerce, traditional markets, restaurants, and supermarkets. The bean sprout products are placed in Sufarm's warehouses located in two different places, namely Parung and Cihowe, which will be distributed to three agents. The delivery of bean sprout products by Sufarm is carried out using land transportation in the form of pickup trucks. The issues faced by Sufarm include scheduling, routes, delivery distances, and delivery costs that are considered suboptimal. This results in irregular delivery routes, schedules, and distances, leading to high distribution costs. Therefore, this research aims to determine the optimal delivery routes based on the distribution costs. Shipping costs are calculated based on the distance between the warehouse and the agents using 3 transportation models, namely the Least Cost method, the North West Corner method, and Vogel’s Approximation Method. The results of the distribution cost calculation using the Least Cost method is Rp268.889, the North West Corner method is Rp225.556, and Vogel’s Approximation method is Rp268.889.